2005
DOI: 10.1097/00019501-200508000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of varicocele in patients with coronary artery ectasia

Abstract: We have shown that patients with coronary artery ectasia have an increased prevalence of varicocele compared to those with coronary artery disease. The mechanism underlying coronary artery ectasia might further increase the prevalence of varicocele in susceptible patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 31 publications
3
46
0
Order By: Relevance
“…8 Varicose veins and varicocele (dilatation of the pampiniform plexus) are significantly higher in CAE, suggesting the possible existence of a generalized defect of the vascular wall. 29,30 …”
Section: Clinical Presentations and Diagnosismentioning
confidence: 99%
“…8 Varicose veins and varicocele (dilatation of the pampiniform plexus) are significantly higher in CAE, suggesting the possible existence of a generalized defect of the vascular wall. 29,30 …”
Section: Clinical Presentations and Diagnosismentioning
confidence: 99%
“…3 Varicoceles are associated with other vas� cular pathologies. 4 Kılıç and colleagues also reported that peripheral varicose veins share a pathological mechanism with varicocele. 5 Mean platelet volume (MPV) is a parameter provided by the automatic blood count device during a routine blood count, but clinicians do not usually pay it much attention.…”
Section: Introductionmentioning
confidence: 96%
“…Likewise, close association has been reported between varicocele and peripheral varicose veins. 2 Furthermore, high prevalence of varicose vein 3 or varicocele 4 has been reported in patients with coronary artery ectasia suggesting common vascular wall pathology. 5 Given the nature of pelvic venous reflux, peripheral varicose vein and haemorrhoids, a systematic approach also needs to be taken into consideration in future studies…”
mentioning
confidence: 99%